A Multi-UAV Co-Simulation Environment for Safety and Performance Analysis - Silva, Leydson; Barros, José de Sousa; Salvador, Ewerton; Nigam, Vivek; Brito, Alisson (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2019: Anais do IX Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2019)
Co-Simulation can provide important insights+G45 on how well mission strategies perform. Simulations can provide insights on which strategies could provide safety guarantees because of the high investments necessary for the creation of a multi-UAV system. We propose a co-simulation framework of multiple UAVs for the analysis of missions in order to evaluate different flight strategies with great efficiency. To make the environment as realistic as possible, we introduced external threats such as winds, sectors with flight restrictions, and aircraft crashes. We validated our framework using a case study of an air surveillance system, where two types of flight strategies comparing two different flight strategies. We can analyze trade-offs between the flight strategies, in terms, of chances of UAV collision, running out of energy, and performing tasks.